2014
DOI: 10.1007/s10956-014-9489-5
|View full text |Cite
|
Sign up to set email alerts
|

Laptop Use, Interactive Science Software, and Science Learning Among At-Risk Students

Abstract: This year-long, quasi-experimental study investigated the impact of the use of netbook computers and interactive science software on fifth-grade students' science learning processes, academic achievement, and interest in further science, technology, engineering, and mathematics (STEM) study within a linguistically diverse school district in California. Analysis of students' state standardized science test scores indicated that the program helped close gaps in scientific achievement between at-risk learners (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…As classrooms continue to change with increasing cultural and linguistic diversity (Kena et al, 2016; McFarland et al, 2017; National Clearinghouse for English Language Acquisition, 2010), a growing body of scholarship continues to suggest the potential of digital tools and multiple modalities for leveraging the varied and robust meaning‐making repertoires of emergent bilinguals (EBs). Special issues of TESOL Quarterly and Journal of Second Language Writing , for example, confirmed the perspective that multiple modalities, including visuals, sound, text, and movement, are not only scaffolds for EBs accessing English but also tools for asserting identities (Ajayi, 2015; Cummins, Hu, Markus, & Montero, 2015), engaging multiple audiences (Kim, 2018; Pacheco & Smith, 2015), and making meaning across disciplines (Goulah, 2017; Grapin, 2019; Zheng, Warschauer, Hwang, & Collins, 2014). Expanded views of literacy (Leu, Kinzer, Coiro, & Cammack, 2004; New London Group, 1996) affirm that communicating through multiple modalities can afford EBs transformative authoring experiences not typically offered by traditional, print‐centric composing pedagogies.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…As classrooms continue to change with increasing cultural and linguistic diversity (Kena et al, 2016; McFarland et al, 2017; National Clearinghouse for English Language Acquisition, 2010), a growing body of scholarship continues to suggest the potential of digital tools and multiple modalities for leveraging the varied and robust meaning‐making repertoires of emergent bilinguals (EBs). Special issues of TESOL Quarterly and Journal of Second Language Writing , for example, confirmed the perspective that multiple modalities, including visuals, sound, text, and movement, are not only scaffolds for EBs accessing English but also tools for asserting identities (Ajayi, 2015; Cummins, Hu, Markus, & Montero, 2015), engaging multiple audiences (Kim, 2018; Pacheco & Smith, 2015), and making meaning across disciplines (Goulah, 2017; Grapin, 2019; Zheng, Warschauer, Hwang, & Collins, 2014). Expanded views of literacy (Leu, Kinzer, Coiro, & Cammack, 2004; New London Group, 1996) affirm that communicating through multiple modalities can afford EBs transformative authoring experiences not typically offered by traditional, print‐centric composing pedagogies.…”
mentioning
confidence: 75%
“…Finally, a few studies explored how EBs engaged with content beyond ELA through creating digital multimodal projects (Cummins et al, 2015; Goulah, 2017; Rao, 2015; Zheng et al, 2014). Cummins and colleagues’ (2015) research on identity texts demonstrated how multilingual students could work toward the dual goals of identity expression and content learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another solution to the tracking problem is offering engaging science activities at all levels; students from low‐achievement track classes succeed when offered exciting technology‐enhanced activities. For example, research has shown that technology facilitated science education can close the science achievement gap between high‐achievement and low‐achievement groups (Zheng, Warschauer, Hwang, & Collins, ). Furthermore, research has demonstrated that game‐based curricula are successful at supporting low‐achievement students in science learning (Sadler, Romine, Stuart, & Merle‐Johnson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of resources and materials that promote math and science learning across different types of schools also partially accounts for differences in the quality of math and science instruction and for differences in levels of interest in STEM. For example, Zheng, Warschauer, Hwang, and Collins () found that the use of computers in classrooms increased math and science achievement as well as interest in the STEM fields. Although there is no certainty that the quantity of resources merely available to schools, teachers, and students has a direct effect on math and science outcomes, it is a fact that resources are enablers that provide the context in which schools operate (Oakes, ).…”
Section: Introductionmentioning
confidence: 99%